Effects of Shadow Training and Leg Muscle Strength on Badminton Footwork Agility: A Factorial Experimental Design - Abang Putra Pratama; Endang Rini Sukamti; Bernadeta Suhartini; Endang Murti Sulistiyowati; Ilham Ilham; Novadri Ayubi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
As badminton significantly emphasizes player footwork’s agility and precision, performing shadow training and increasing leg muscle strength are believed to increase players’ agility. However, despite recognizing the importance of both training methods in enhancing athletic performance, there is a lack of comprehensive understanding regarding their combined effects on a player's agility during gameplay. This study aimed to analyze group disparities in shadow training while considering varying levels of leg muscle strength and their impact on badminton players' footwork agility. The shadow training groups encompassed those using reaction lights and those under coach direction, while leg muscle strength was categorized as either high or low. Employing an experimental approach with a 2 x 2 factorial design, the study randomly selected 20 students aged 15.3±7.2. Shadow training was conducted in three sessions per week for approximately six weeks. This training focused on rapid/explosive movements. Data on muscle strength and agility were gathered using a leg dynamometer test and a foot exercise test. They were then statistically analyzed using two-way ANOVA at a significance level of 0.05. The results suggest that shadow training with reaction lights is more effective for individuals with high leg muscle strength. Meanwhile, shadow training with a coach’s direction may yield better results for those with low leg muscle strength. However, both training modalities can be beneficial for individuals with low leg muscle strength. These findings provide valuable insights for coaches and badminton instructors in devising tailored training programs to enhance footwork agility.